ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN STRUKTUR MODAL DENGAN UKURAN DAN UMUR PERUSAHAAN SEBAGAI VARIABEL KONTROL (STUDI PADA PERUSAHAAN MANUFAKTUR DAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019) - Alexander Natanael Silaban; Irene Rini Demi Pangestuti (Diponegoro Journal of Management, 2022)
This research aims to examine the main factors that influence capital structure policy proxied by debt ratio (DR) especially in manufacturing and energy companies listed on the Indonesia Stock Exchange (IDX) during 2015-2019. The population of this research consists of manufacturing and energy companies listed on IDX in year 2015-2019. This research used secondary data and purposive sampling method to determine the study sample. The total samples in this study are 16 companies. Multiple Regression is used as the analysis technique in this research. The study documents the negative significant effect of profitability, liquidity, and non-debt tax shield on capital structure policy. Conversely, tangibility and cash flow volatility have the positive significant effect on capital structure policy. Moreover, growth has no significant effect on capital structure policy. As a control variables, firm size and company age have a good function in controlling the effect of independent variables on dependent variable.